Profil Pasien Diabetes Melitus Tipe 2 di RSUD X Bogor, Jawa Barat - Dwi Agustina; Eddy Rosfiati (STIKes Persada Husada Indonesia, 2018)
Non-communicable disease (NCD) is a disease that often occurs worldwide even in Indonesia. One of the most common NCD is diabetes mellitus (DM). DM is a disease caused by insulin deficiency or damage to the effect of increased blood sugar or glucose level. Factors that influence the emergence of DM include age, gender and obesity. DM patients will seek medical help at the hospital when complications encountered. The aim of the study was to seek for a characterictic picture, supporting assessment results, incidentces of diabetic wound complications, length of inpatient stay and discharge status. This study used an observational method with a cross sectional design using secondary data from medical record. Population of DM patients admitted to hospital during trimester was 115 patients. Number of sample in this study were 99 patients. The result of this study showed that DM patients were predominantly women (63.6%) with an age range of 46-55 years (45.5%), decreased hemoglobin level (55.6%), increased leukocytes level (78.8%), normal platelet level (54.5%), length of stay less than 9 days was 64.6%, incidence of diabetic wound complication was 97% and discharge status as indicated by 72.7%.